ANALISIS KESANTUNAN BERBAHASA DALAM PROSES PEMBELAJARAN SISWA KELAS 5 SEKOLAH DASAR - Rani Susanti (Universitas Muria Kudus, 2023)
This study aims to describe the form of compliance and violation of the principle of language guidance in students of class V elementary school N 2 Jambu Mlonggo Jepara with a total of 25 students. In the school environment, students are expected to be able to control what is said.Because the school environment is where students study and form character. Language guidance becomes the basis for the assessment of a person's character. But in fact in the teaching process there are still some students who use disrespectful language to tem. This research method uses a qualitative descriptive approach. Research data collected in the form of recordings of dialogue and student consultation with fellow students and students with teachers. Data collection in this study used observation methods, recording techniques, and interviews. From the results of the study found that there are speech students who adhere to the maxim of wisdom, maximal generosity, maximal appreciation, maximality, maximality, maximal agreement, and maximsimistic. However, there are also student speeches that violate these maxims.